Pemilihan Ikan Segar Berdasarkan Evaluasi Kualitas Sensori: Edukasi Siswa Madrasah Aliyah - A. Dali, Faiza (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Besides being a primary source of protein, fish play a role in the economy of coastal communities and consumption culture in Indonesia. The main issue that needs to be addressed is the lack of public understanding, especially among students, about choosing fresh and high-quality fish. The public does not have adequate knowledge about the sensory quality of fish, such as texture, smell, and color, which are the main indicators of freshness. As a result, consuming low-quality fish can impact health and reduce the nutritional value received. This activity aims to develop students' ability to identify fresh fish based on sensory quality. The approach was carried out through education using PowerPoint media that presents the material visually and interactively. The material includes the characteristics of fresh fish, the importance of choosing quality fish, and a sensory observation guide. The pre-activity test results indicate that the majority of students have minimal understanding in identifying fresh fish. After the presentation of the material, the results indicated an improvement ranging from 5.0 to 68.42%. Students provided positive feedback on the visualizations used in the presentation. This activity successfully raised students' awareness about the importance of the sensory quality of fresh fish for health and daily life.